2022
DOI: 10.3390/ijerph19084613
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Patient Education for Fibromyalgia during Spa Therapy: The FiETT Randomized Controlled Trial

Abstract: Spa therapy is known to improve quality of life and diminish pain. We assessed the efficacy (Fibromyalgia Impact Questionnaire-FIQ) and safety at 6 months of a fibromyalgia-specific therapeutic patient education (TPE) program added to fibromyalgia-specific standardized spa therapy (SST), compared to SST alone, in a controlled randomized trial. We enrolled 157 patients, mostly women, attending spa centers in Southwest France in 2015–2016, and randomized them to SST + TPE (79) or SST (78). The intention-to-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In summary, only 8.6% (9 studies) of the studies covered all mandatory domains as recommended by OMERACT [ 26 , 31 , 41 , 42 , 75 , 76 , 87 , 112 , 130 ] and only 6.7% (7 studies) covered all mandatory and optional domains [ 26 , 31 , 41 , 42 , 76 , 112 , 130 ]. Remarkably, although the OMERACT recommendations have been available since 2009 [ 5 ], only eight studies referred to those recommendations in the methods section or in the discussion [ 30 , 56 , 73 , 79 , 80 , 113 , 125 , 126 ]. Seven studies cited the OMERACT core set because they explicitly conformed to their recommendations [ 30 , 56 , 73 , 80 , 113 , 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, only 8.6% (9 studies) of the studies covered all mandatory domains as recommended by OMERACT [ 26 , 31 , 41 , 42 , 75 , 76 , 87 , 112 , 130 ] and only 6.7% (7 studies) covered all mandatory and optional domains [ 26 , 31 , 41 , 42 , 76 , 112 , 130 ]. Remarkably, although the OMERACT recommendations have been available since 2009 [ 5 ], only eight studies referred to those recommendations in the methods section or in the discussion [ 30 , 56 , 73 , 79 , 80 , 113 , 125 , 126 ]. Seven studies cited the OMERACT core set because they explicitly conformed to their recommendations [ 30 , 56 , 73 , 80 , 113 , 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, although the OMERACT recommendations have been available since 2009 [ 5 ], only eight studies referred to those recommendations in the methods section or in the discussion [ 30 , 56 , 73 , 79 , 80 , 113 , 125 , 126 ]. Seven studies cited the OMERACT core set because they explicitly conformed to their recommendations [ 30 , 56 , 73 , 80 , 113 , 125 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized controlled trial, an FM-specific therapeutic education program added to spa therapy showed benefits in quality of life and pain intensity compared to standard therapy alone [ 139 ]. At 6 months, the physical exercises taught during the education program were still practiced regularly by 87% of patients [ 139 ].…”
Section: Spa Therapy Effects On Frailty In Rheumatic Diseases: Clinic...mentioning
confidence: 99%
“…In a randomized controlled trial, an FM-specific therapeutic education program added to spa therapy showed benefits in quality of life and pain intensity compared to standard therapy alone [ 139 ]. At 6 months, the physical exercises taught during the education program were still practiced regularly by 87% of patients [ 139 ]. Furthermore, the combination of low-dose radon treatment, physical exercise, massages, mud therapy, prevention strategies, education strategies and healthy nutrition demonstrated some beneficial effects in FM patients [ 124 ].…”
Section: Spa Therapy Effects On Frailty In Rheumatic Diseases: Clinic...mentioning
confidence: 99%
“…Several large randomized controlled trials have demonstrated the benefit of balneotherapy in several conditions: musculoskeletal conditions [2][3][4][5][6][7], venous conditions [8], stress-related disorders [9], overweight and metabolic syndrome [10][11][12], post-breast cancer [13][14][15] and neurodegenerative disorders [16]. Papers have also been published on "therapeutic patient education" for fibromyalgia [17], venous insufficiency [18], chronic low back pain [19], physical activity [20,21] or psychotropic withdrawal [22]. The medical literature also provides scientific evidence of resource-saving and less medication [9,23,24] and suggests fewer hospital stays [16,25] thanks to spa therapy.…”
Section: Introductionmentioning
confidence: 99%